Global prevalence of spondyloarthritis in low-income and middle-income countries: a systematic review and meta-analysis protocol. Issue 10 (29th October 2020) - Allado, Edem; Moussu, Anthony; Bigna, Jean Joel; Hamroun, Sabrina; Camier, Aurore; Chenuel, Bruno; Hamroun, Aghiles
Abstract : Introduction: In the past decade, the definition of spondyloarthritis (SpA) has undergone major modifications with respect to new diagnostic tools and classifications. With the advent of biotherapies, treatment possibilities in patients with SpA have substantially improved in the last few years. There is great interest in obtaining accurate data on the disease prevalence, especially in regions where data remains scarce such as low-income and middle-income countries (LMICs), in order to measure and understand the needs of their healthcare systems. Therefore, through a global systematic review and meta-analysis, the current study aims to investigate the prevalence of SpA and human leucocyte antigen B27 (HLAB27) and its association with the risk of SpA in the LMIC population. Methods and analysis: We will include cohort, case–control and cross-sectional studies performed among adults (>15 years) living in LMICs. EMBASE, Medline, Global Index Medicus and Web of Knowledge will be searched for relevant records published until 30 April 2020, without any language restriction. The review will be reported according to the Meta-analysis Of Observational Studies in Epidemiology (MOOSE) guidelines. After screening of titles and abstracts, study selection, data extraction and risk of bias assessment by two independent reviewers, we shall assess the studies individually for clinical and statistical heterogeneity. Random-effect meta-analysis will be used to pool studies judged to be clinically homogeneous. Egger's test and visual inspection of funnel plots will be used to assess publication bias. Results will be presented by WHO subregions. Ethics and dissemination: Since primary data is not collected in this study, ethical approval is not required. This review is expected to provide relevant data on the epidemiology of SpA, HLAB27 and their association in the global population of LMICs. The final report will be published in a peer-reviewed journal. PROSPERO registration number: CRD42020163898.